The Spanish occupation in western Algeria between the resistance of the Algerians and the spanish crown stuck to Oran (1509-1792) - bearcia, Sabah (The Algerian Historical Journal, 2026)
This scientific paper is a view of local and especially foreign sources, the Spanish occupation of a part of western Algeria. We tried to look of the other side (the Spaniards). This research aims to study the conditions of each of the Algerians who were adjacent to the areas occupied by the Spaniards in western Algeria at the beginning of modern times. We have come to the conclusion that the situation of the Algerians in these areas was lighter than that of the Spaniards in their forts and that the length of time they stayed in Algeria cost them a lot of losses and suffering, and it was a desperate attempt to keep the occupied territories, even though it did not bring them gold or silver, as happened with their colonies in the New World, but for geostrategic calculations, it lost its importance in the 18th century AD